2012
DOI: 10.1159/000337713
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Depot Medroxyprogesterone Acetate versus Continuous Oral Contraceptive Pills in the Treatment of Endometriosis-Associated Pain: A Randomized Comparative Trial

Abstract: Background/Aim: To evaluate the efficacy and tolerability of postoperative depot medroxyprogesterone acetate (DMPA) versus postoperative continuous oral contraceptive (OC) pills in the treatment of endometriosis-associated pain. Methods: After a conservative surgery, 84 patients with symptomatic endometriosis were randomized to receive either intramuscular DMPA (150 mg) every 12 weeks for 24 weeks or continuous OC pills (ethinyl estradiol 0.03 mg and gestodene 0.075 mg) daily for 24 weeks. At weeks 12 and 24 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 41 publications
0
9
0
4
Order By: Relevance
“…Early observational studies suggest that in women with stage III/IV endometriosis without other identifiable infertility factors, conservative surgical treatment with laparoscopy and possibly laparotomy increases fertility [11,12]. Postoperative medical treatment has been used to release endometriosis-associated pain, suppress disease development and prevent recurrence [13], but it does not improve natural PRs. A meta-analysis of 12 studies comparing surgery plus hormonal treatment versus surgery plus placebo or no treatment showed no difference in PRs [14], which is consistent with our study results (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Early observational studies suggest that in women with stage III/IV endometriosis without other identifiable infertility factors, conservative surgical treatment with laparoscopy and possibly laparotomy increases fertility [11,12]. Postoperative medical treatment has been used to release endometriosis-associated pain, suppress disease development and prevent recurrence [13], but it does not improve natural PRs. A meta-analysis of 12 studies comparing surgery plus hormonal treatment versus surgery plus placebo or no treatment showed no difference in PRs [14], which is consistent with our study results (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Some are aimed at imitating periods during which a woman menopauses, example for GnRH analogues or danazol. Some are in light of mimic periods in which a woman is pregnant, such as oral contraceptives or progestins [22,23,24]. The others are directed against endometriotic estrogen synthesis [25], including Anastrozole and letrozole [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…nausea, headaches, depression, weight gain, thromboembolism) might limit the usage of these drugs [1,2,3,4,5]. …”
Section: Discussionmentioning
confidence: 99%
“…Dysmenorrhea also has a negative impact on quality of life [2,3,4]. Primary dysmenorrhea is not associated with any identifiable pelvic disease.…”
Section: Introductionmentioning
confidence: 99%